Cultural Map Based on Smart-Disc Audiovisual on the Diversity of Social Studies Learning Culture for Grade IV Elementary Students - Pangestu, Ida Bagus Gede Surya (Universitas Pendidikan Ganesha, 2021)
The problem in this study is the less of use instructional media and the less interested students in learning, so media is needed to attract students' interest in learning enthusiasm. This study aims to develop an audiovisual smart disk-based cultural map learning media on the material on the diversity of social studies learning culture. This research is a development research using the ADDIE model. The subject of this research is the validity of the smart disk audiovisual based cultural map learning media with the subject of the trial are 1 subject expert, 1 learning design expert, 1 instructional media expert, and 3 students for individual trials. The data collection method used in this study is use the non-test method with a questionnaire as an instrument. The data analysis technique used in this study is the quantitative statistical analysis technique. The results of this development indicate that the validation results of subject content experts get a percentage of 87.50% (very good); learning design experts get a percentage of 91.66% (very good); instructional media experts get a percentage 91.66% (very good) and; individual test results obtained a percentage of 91.33% (very good). So it can be concluded that the smart disk audiovisual based cultural map learning media is valid and feasible to use. The implication of this research is that the smart disk audiovisual based cultural map learning media can be used as a learning medium so that it can attract students' interest in learning.